Insights into amyloid fibril formation from mass spectrometry. - Caddy, G; Robinson, C (2006)
Mass spectrometry has become increasingly important in amyloid research specifically in the mechanism of formation and characterization of fibrils. In this review we highlight key experiments that provide evidence for different conformations, interactions and unfolding intermediates in proteins associated with amyloid diseases.